Severe Retinopathy of Prematurity Is Not Independently Associated With Worse Neurodevelopmental Outcomes in Preterm Neonates - Altendahl, Marie; Sim, Myung Shin; Kokhanov, Artemiy; Gundlach, Bradley; Tsui, Irena; Chu, Alison (Frontiers in Pediatrics, 2021)
Purpose: To evaluate the relationship between retinopathy of prematurity (ROP) severity and neurodevelopmental outcomes in premature neonates at 0-36 months corrected age. Methods: A retrospective chart review was performed on 228 neonates screened for ROP at the UCLA Mattel Children’s Hospital between 2011-2018. Demographic information, clinical outcomes, ROP severity (no ROP, type 1 ROP, type 2 ROP), and Bayley-III neurodevelopmental scores were collected. Infants were grouped into corrected age cohorts (0-12 months, 12-24 months, and 24-36 months) to assess neurodevelopmental outcomes with increasing age. Within each age cohort, ANOVA and Chi-Square testing were used to detect differences in birth characteristics and neurodevelopmental scores between infants with type 1 ROP, type 2 ROP, or no ROP. Univariable analyses assessed the relationship between ROP severity and neurodevelopmental outcomes within each age cohort. A multivariable analysis was then performed to determine if ROP severity remained significantly associated with worse neurodevelopmental scores after controlling for birth weight (BW), intraventricular hemorrhage grade (IVH), health insurance type, male sex, and age at Bayley testing. Results: Without controlling for factors associated with prematurity, neonates with type 1 ROP had poorer cognition (p=0.001) and motor (p=0.006) scores at ages 0-12 months and poorer cognition (p=0.01), language (p=0.04) and motor (p=0.04) scores at ages 12-24 months than infants without ROP, but no significant differences were detected at ages 24-36 months. After adjusting for BW, IVH, insurance type, male sex, and age at Bayley testing, ROP severity was no longer associated with worse neurodevelopmental scores in any domain. Conclusion: This study emphasizes that poorer neurodevelopmental outcomes in preterm neonates are most likely related to lower birthweight, associated co-morbidities of prematurity, and socioeconomic factors such as health insurance, not severity of ROP itself.